Model Pendampingan Kewirausahaan Sosial Pada Pengelolaan Program PKBM Anging Mammiri Kabupaten Gowa - Fatmawati Gaffar; Rudi Amir; Kartini Marzuki (Universitas Negeri Makassar, 2023)
The purpose of the study was to obtain data on the Social Entrepreneurship Assistance Model in Increasing Entrepreneurial Independence in the Management of the Anging Mammiri PKBM Program, Gowa Regency, by describing in the form of data the results of research conducted through a qualitative approach. In particular, this study aims to describe as follows: 1) Design of a social entrepreneurship mentoring model in increasing entrepreneurial independence in program management, 2) Determinants that are determinants of the success of program management. This research uses a qualitative approach with a type of case study research. The data is analyzed descriptively, in-depth and comprehensively consisting of reduction, data display and drawing conclusions. The results of research on the social entrepreneurship assistance model in the management of PKBM in improving the quality of institutions in PKBM Anging Mammiri, Gowa Regency provide an illustration that: 1) there is planning, implementation, results and assessment of management periodically and continuously, 2) the role of managers in order to improve the quality of the institution, 3) qualifications for the level of education p engelola and p endidik, 4) the support of community leaders is quite high 5) the facilities and infrastructure to support learning facilities are quite feasible, and the learning environment is quite conducive in Anging Mammiri, Gowa Regency